PROBING DETERMINANTS OF UNIVERSITY ACADEMICIANS’ KNOWLEDGE SHARING INTENTION - Chin, Tay Lee; Yean, Tan Fee; Leow, Hon-Wei (International Journal of Application on Economics and Business, 2023)
The determinants of information sharing intention are identified in this paper (i.e., managerial support, interpersonal trust, and reciprocity). Data were collected from questionnaires from academicians in the Malaysian private universities. Multiple regression analysis was performed to test the analysis. Management support, interpersonal trust and reciprocity positively influence knowledge sharing intention. The results revealed management support, interpersonal trust and reciprocity play significant roles in determining academicians’ knowledge sharing intentions. Based on the insights of social exchange theory, this study discovered that strong effects of managerial support, interpersonal trust, and reciprocity on information sharing intention. Hence, social exchange theory is extended to the knowledge sharing intention among academicians’ universities. For the university to encourage knowledge sharing intention, they may improve their current management style and maintain a work environment that encourages employees to trust each other.